2013
DOI: 10.5171/2013.476066
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management Implementation in a Government Research Institute in Selangor, Malaysia

Abstract: Knowledge is recognised as an important asset in any organisations these days. Unfortunately, many organisations are not doing enough to effectively manage this important asset in creating and maintaining their competitive advantage. The objective of this study was to investigate the implementation of knowledge management in a government research institute in Selangor, Malaysia. This explorative study employs both quantitative and qualitative approaches to achieve the research objectives. A set of questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…The present study has shown that KM implementation is highly linked to policies, budgets, human resource, processes, and technology. It is different from the findings of Ramin et al (2013) in which there are three main determinants, namely, organization, human resources, and technology, for the implementation of KM in companies. Nevertheless, the present study confirms the findings of Savitri et al (2013) in which the interactions between human resources, processes, and technology are the key factors in organizational KM, and a systematic approach is insufficient for carrying out KM processes and the absence of learning and cultural sharing are the main reasons behind the sub-optimal KM implementation in higher education institutions.…”
Section: University Scopuscontrasting
confidence: 87%
“…The present study has shown that KM implementation is highly linked to policies, budgets, human resource, processes, and technology. It is different from the findings of Ramin et al (2013) in which there are three main determinants, namely, organization, human resources, and technology, for the implementation of KM in companies. Nevertheless, the present study confirms the findings of Savitri et al (2013) in which the interactions between human resources, processes, and technology are the key factors in organizational KM, and a systematic approach is insufficient for carrying out KM processes and the absence of learning and cultural sharing are the main reasons behind the sub-optimal KM implementation in higher education institutions.…”
Section: University Scopuscontrasting
confidence: 87%
“…This study finds that the success of KM implementation depends on policies, budgets, people, processes, and technology. The different research conducted by Ramin, Taib (2013) which shows that three main factors influencing the implementation of KM in University. There is an ebook/dp/B000PY4HW8/ref=sr_1_1?s=books&ie=UTF8&qid=1545101059&sr=1-1&keywords=Bryan+Bergeron%2C+Essentials+of+Knowledge+Management.…”
Section: The Reality Of Knowledge Flow In Islamic Higher Educationmentioning
confidence: 99%
“…Under this circumstance, this study investigates the practices of sustainable competitive advantage strategies among different categories of Government-Linked Companies (GLCs) in Malaysia. Organizational learning is considered one of the most important elements to gain a sustainable competitive advantage (Kloot, 1997;Garavan, 1997;Choe, 2002;Ramin et al, 2013). According to Purhaghshenas and Esmatnia (2012), learning processes occur when there is a change in ideas and viewpoints in the organization.…”
Section: Introductionmentioning
confidence: 99%